Optimization Of Parameters Of A Rod Intensifier Of A Potato Digger With The Method Of Mathematical Planning (Texas Journal of Engineering and Technology, 2024)
In this article, the method of mathematical planning of multifactorial experiments is used to determine the optimal values of the parameters of a potato digger equipped with an elastic rod intensifier, obtained in single-factorial experiments. It is assumed that the influence of factors on the evaluation criteria is fully explained by a second-order polynomial, and the experiments were carried out according to the Hartley-4 (X4) plan